THE RELATIONSHIP BETWEEN DURATION OF FIXED ORTHODONTIC TREATMENT WITH PERIODONTAL STATUS AND TREATMENT NEEDS AMONG STUDENTS IN THE FACULTY OF DENTISTRY UNIVERSITAS MUSLIM INDONESIA MAKASSAR IN 2017 - Triana Amaliah Jayanti; Yustisia Puspitasari; Nurfadhilah Arifin (FKG Unlam, 2018)
Background: The interest and awareness for maintaining oral health is increasing. It is not only confined to fillings and extractions, but also extend to orthodontic treatment. Orthodontic treatment aims to get normal occlusion, improves the health of the periodontal, dental health and facial aesthetics. Increased interest in orthodontic treatment was due to the high prevalence of malocclusion. The prevalence of malocclusion in Indonesian is still very high which is about 80% of the population. Orthodontic treatments change the circumstances surrounding the oral cavity, so that orthodontic appliance users who do not maintain oral hygiene are at risk for periodontal disease. Objective: to determine relationship between duration of the fixed orthodontic treatment with periodontal status and treatment needs among students in the Faculty of Dentistry, Universitas Muslim Indonesia Makassar in 2017. Materials and methods: This study is observational analytical study with cross sectional study design. The samples were 35 students in Faculty of Dentistry UMI Makassar using fixed orthodontic appliance. The method of data collection that checks the periodontal status and treatment needs was done by using an a Community Periodontal Index of Treatment Need (CPITN). The statistical analysis was done by using Chi-Square test. Results: Based on the statistical test, it is shown that there were relationship between duration of fixed orthodontic treatment with periodontal status (p = 0,004 < 0,01) and the periodontal treatment need (p = 0,004 < 0,01). Conclusion: There is relationship between duration of fixed orthodontic treatment with periodontal status and treatment needs of the students in the Faculty of Dentistry, Universitas Muslim Indonesia in 2017.